Study design and procedures for a hybrid effectiveness-implementation incomplete stepped-wedge cluster-randomized trial to evaluate a differentiated point-of-care HIV diagnosis and management model for the prevention of vertical transmission of HIV in Malawi: The PAC-Man trial protocol - Michael E. Herce; Caitlin Cassidy; Alexandra Munson; Jessie K. Edwards; Sarah E. Rutstein; Mitch Matoga; Chimwemwe Kumwenda; Katherine R. Simon; Joep J. van Oosterhout; Carrie M. Cox; Funny Kamanga; Wiza Kumwenda; et al. (Implementation Science Communications)
Abstract Background In Malawi and elsewhere in Africa, many children living with HIV are unaware of their status, often because of missed services for the prevention of vertical transmission of HIV (PVTH). Pregnant and breastfeeding women (PBFW) living with HIV frequently go without viral load (VL) monitoring and their infants miss key HIV testing milestones for early infant HIV diagnosis (EID). In Malawi, the current standard of care (SOC) involves mostly passive approaches to pediatric HIV diagnosis, relying on mothers presenting to health facilities with their infants. To reach PBFW living with HIV and their infants who miss critical HIV services and who are at higher risk for adverse HIV outcomes, including vertical transmission, we developed the “Point-of-care Active Case finding & Management” or “PAC-Man” model. PAC-Man uses a multifaceted implementation strategy involving task-shifted mobile teams to reach these mother-infant pairs (MIPs) with evidence-based point-of-care (POC) technology for EID and maternal VL testing in the community, linked to back-to-care and antiretroviral therapy (ART) services. Methods We will conduct a hybrid type III effectiveness-implementation incomplete stepped-wedge cluster-randomized trial in 12 clinics in Malawi over a 3-year period to test our strategy. Control periods will reflect SOC. Intervention periods will add PAC-Man to SOC. The primary outcome is reach of infant EID testing by age 6 months in the clinic population. Secondary outcomes include the proportion of infants newly diagnosed with HIV initiating ART and maternal VL testing reach. These outcomes will be assessed using routinely collected clinic data augmented with field surveys enrolling a sample of MIPs randomly selected from each clinic. Implementation outcomes of acceptability, adoption, fidelity, implementation, sustainability, cost, and scalability will be assessed using convergent mixed methods. Discussion Study findings will offer new insights into the effects of differentiated, community-based services for reaching infants unaware of their HIV-positive status and their mothers and characterize the fit of the PAC-Man strategy with the national PVTH program. The study holds promise for improving access to EID and VL testing, and ART, for MIPs currently being missed by traditional facility-based approaches and could suggest a novel approach for use in real-world PVTH programs across Africa. Trial registration This study is registered at ClinicalTrials.gov, NCT06493357.